Why emotions need to labor—Influencing factors and dilemmas in the emotional labor of Chinese English teachers teaching online - Wang, Huaidong; Song, Nuankun (Frontiers in Psychology, 2022)
During the COVID-19, online teaching has become a popular way of teaching in the world. Previous research on English language teachers’ emotional labor has not focused on the changes brought about by online teaching. Unlike the traditional physical teaching space, the emotional labor of English teachers teaching online changes with the daily use of online technological conditions. Therefore, this paper aims to investigate the factors influencing teachers’ emotional labor in online teaching and the emotional labor dilemmas. We took interviews with a group of English teachers in China (T1, T2, …T20) and found that their online teaching emotions were influenced by three main factors: the degree of adaptation to online teaching technology, the invisibility of the online teaching space, and the peripheral environment of the space in which the teachers were located. In addition, this study observed the online classrooms of the interviewees and found that the first two influences are at a priority level for Chinese English teachers, while whether the third factor can bring positive or negative emotions is often influenced by the nature of the emotions brought by the first two factors. In order to find a balance between norms and emotions, English teachers are often accompanied by emotional labor in their work. However, they face many dilemmas of choice and behavior during the emotional labor of teaching online: emotional rule dilemma, emotional expression dilemma and professional identity dilemma. The emergence of these dilemmas is directly related to the influencing factors. In conclusion, this article uses normative and emotional labor theories to explore how norms affect Chinese English teachers’ emotions when teaching online as a response to the question of why emotions need to be labored. Ultimately, this study offers some useful suggestions for language teachers’ emotional labor dilemmas.